The existence of solutions for dynamic inclusions on time scales via duality - Girejko, E.
The problem of the existence of solutions to nabla differential equations and nabla differential inclusions on time scales is considered. Under a special form of the set-valued constraint map, sufficient conditions for the existence of at least one solution, that stays in the constraint set, are derived. © 2011 Elsevier Ltd. All rights reserved.